Data of Atlantic cod stock - Sguotti, Camilla; Otto, Saskia; Frelat, Romain; Langbehn, Tom; Plambech Ryberg, Marie; Lindegren, Martin; Durant, Joel; Stenseth, Nils; Möllmann, Christian (Dryad Digital Repository, 2019)
Here the data of Spawning Stock Biomass (SSB), Fishing Mortality (F) and Sea Surface Temperature (SST) for the 19 cod stocks used in the study can be found. SSB and F derived from stock assessment developed by the institutions across the North Atlantic: ICES, NAFO, DFO and NOAA. The SST were collated from the NOAA Extended Reconstructed Sea Surface Temperature dataset (ERSST, www.ncdc.noaa.gov) version 4.